Scrofuloderma and Sweet's syndrome - Punkae Mahaisavariya (2018)
Background: In recent years, the rare association of Sweet's syndrome with nontuberculous mycobacterial lymphadenitis has been reported. Objective: To report the clinical, demographic, and bacteriologic data and association with Sweet's syndrome of 18 patients with scrofuloderma and scrofuloderma-like condition caused by nontuberculous mycobacterial infections seen during the past 7 years (1994-2000). Methods: In all patients, a biopsy specimen was obtained for histopathologic and microbiologic studies. Patients from whom Mycobacterium tuberculosis and nontuberculous mycobacteria were isolated from the culture of skin biopsy specimens were included. Deep fungal infection was excluded by the lack of a fungal element in histologic section and cultural methods. The patients were treated with antimicrobials or antituberculous drugs according to the causative species. Results: Eighteen cases of scrofuloderma (nine male, nine female; mean age, 36.9 years) were found among 104 patients with cutaneous tuberculosis and nontuberculous mycobacterial cutaneous infections. Sixteen of the 18 cases had lymphadenitis as the underlying focus of scrofuloderma: 15 cases occurred in the cervical group and one case in the inguinal area. One case drained from the soft tissue and one from the paranasal air sinus. Five cases had multiple episodes of Sweet's syndrome during the course of treatment. Most cases in this group (four of the five) were middle-aged women with cervical lymphadenitis, and the most common species were rapid growers. Conclusions: Age, sex, and the site of infection may have some influence on the association with Sweet's syndrome in nontuberculous mycobacterial infections.